Konsep Nilai Wajar (Fair Value) dalam Standar Akuntansi Berbasis IFRS di Indonesia Apa dan Bagaimana? - W., Heri Sukendar (Bina Nusantara University, 2012)
This paper is intended to explain the use of the concept of fair value instead of book value. The accounting world in Indonesia during the last few years have made convergency implementation of new accounting standards oriented to the International Financial Reporting Standards (IFRS) issued by International Accounting Standard Boars (IASB). This new accounting standard that emphasizes the concept of fair value compared with book value concept is outdated. The use of the concept of fair value of the difference and it turned out to be a trigger konvergency change the paradigm of the book value of a simpler, but less information is less transparent. The implementation of accounting standards konverjensi done gradually raises serious problems, this can be seen from postponed the application of PSAK 50 & PSAK 55 in the banking industry. Knowledge and experience of inadequate is a priority of fair value implementation difficulties.